Reaksi Pasar terhadap Pengumuman MSCI Freeze Indonesia: Studi Peristiwa pada Pasar Modal Indonesia - ADRIANDA ANWAR; Nila Rahayu; I Gusti Agung Arista Pradnyani; Yeldi Dwi Genadi (Jurnal Aplikasi Perpajakan, 2026)
This study aims to analyze market reactions to the announcement of MSCI Freeze Indonesia on stocks included in the MSCI Indonesia Index. Market reactions are measured using abnormal return (AR), trading volume activity (TVA), stock volatility, average abnormal return (AAR), and cumulative abnormal return (CAR). This study employs a quantitative approach using the event study method. The sample consists of 17 constituent stocks of the MSCI Indonesia Index selected through purposive sampling. The observation period uses an eleven-day event window, consisting of five trading days before the announcement (t-5), the announcement day (t0), and five trading days after the announcement (t+5). Data were analyzed using Paired Sample t-Test, Wilcoxon Signed Rank Test, and One Sample Test. The results indicate that there is no significant difference in abnormal return before and after the MSCI Freeze Indonesia announcement. In addition, Average Abnormal Return (AAR) and Cumulative Abnormal Return (CAR) during the observation period are also not statistically significant. In contrast, trading volume activity and stock volatility show significant differences following the announcement. These findings suggest that the MSCI Freeze Indonesia announcement does not significantly affect stock returns but influences trading activity and investors’ risk perception. Therefore, market reactions to the MSCI Freeze Indonesia announcement are more strongly reflected in changes in trading behavior and stock volatility than in direct stock price movements.